Réponses

Meilleure réponse !
2014-09-20T19:05:33+02:00


A = (-0,75) + 5,3 + 0,75 + 0,7

A = 5,3 + 0,7 + 075 - 0,75

A = 6 + 0

A = 6


B = 12,6 - 3,9 + 1,4 - 1,1 + 2

B = 12,6 + 1,4 - 3,9 - 1,1 + 2

B = 14 - 5 + 2

B = 11


C = 121 - (-79) + (-11) + 21 - 110

C = 121 + 79 - 11 + 21 - 110

C = 200 - 22 - 110

C = 178 - 110

C = 68


D = - 3,4 - 5,2 + 7,4 + 7,2 - 2,6

D = - 3,4 - 2,6 + 7,2 - 5,2 + 7,4

D = - 6 + 2 + 7,4

D = -4 + 7,4

D = 3,4

2014-09-20T19:14:23+02:00

Bonsoir


A = (-0,75) + 5,3 + 0,75 + 0,7

 = 5,3 + 0,7 + 0,75 - 0,75

 = 6 + 0

 = 6


B = 12,6 - 3,9 + 1,4 - 1,1 + 2

 = 12,6 + 1,4 - 3,9 - 1,1 + 2

 = 14 - 5 + 2

 = 11


C = 121 - (-79) + (-11) + 21 - 110

= 121 + 79 - 11 + 21 - 110

 = 200 - 22 - 110

 = 178 - 110

 = 68


D = - 3,4 - 5,2 + 7,4 + 7,2 - 2,6

= - 3,4 - 2,6 + 7,2 - 5,2 + 7,4

= - 6 + 2 + 7,4

= -4 + 7,4

= 3,4